Curcumin prevents obesity by targeting TRAF4‐induced ubiquitylation in m6A‐dependent manner. (20th April 2021) - Chen, Yushi; Wu, Ruifan; Chen, Wei; Liu, Youhua; Liao, Xing; Zeng, Botao; Guo, Guanqun; Lou, Fangfang; Xiang, Yun; Wang, Yizhen; Wang, Xinxia
Abstract: Obesity has become a major health problem that has rapidly prevailed over the past several decades worldwide. Curcumin, a natural polyphenolic compound present in turmeric, has been shown to have a protective effect on against obesity and metabolic diseases. However, its underlying mechanism remains largely unknown. Here, we show that the administration of curcumin significantly prevents HFD‐induced obesity and decreases the fat mass of the subcutaneous inguinal WAT (iWAT) and visceral epididymal WAT (eWAT) in mice. Mechanistically, curcumin inhibits adipogenesis by reducing the expression of AlkB homolog 5 (ALKHB5), an m 6 A demethylase, which leads to higher m 6 A‐modified TNF receptor‐associated factor 4 (TRAF4) mRNA. TRAF4 mRNA with higher m 6 A level is recognized and bound by YTHDF1, leading to enhanced translation of TRAF4. TRAF4, acting as an E3 RING ubiquitin ligase, promotes degradation of adipocyte differentiation regulator PPARγ by a ubiquitin–proteasome pathway thereby inhibiting adipogenesis. Thus, m 6 A‐dependent TRAF4 expression upregulation by ALKBH5 and YTHDF1 contributes to curcumin‐induced obesity prevention. Our findings provide mechanistic insights into how m 6 A is involved in the anti‐obesity effect of curcumin. SYNOPSIS: Curcumin exerts its anti‐obesity effect by increasing the ALKBH5‐mediated m 6 A modification of TRAF4 mRNA, and enhancing TRAF4 translation in an YTHDF1‐dependent manner. TRAF4 in turn promotes ubiquitination of PPARγ and inhibits adipogenesis. Curcumin feeding prevents HFD‐induced obesity and metabolic dysfunction in mice. Curcumin feeding increases m 6 A modified RNA levels in iWAT and eWAT and decreases ALKBH5 levels in mice. Decreased ALKBH5 protein results in higher m 6 A modification of TRAF4 mRNA, which is recognized and bound by YTHDF1, leading to enhanced translation of TRAF4 in adipocytes. TRAF4, acting as an E3 RING ubiquitin ligase, promotes ubiquitination of PPARγ, leading to lower PPARγ level and inhibits adipogenesis in adipocytes. Abstract : Curcumin exerts its anti‐obesity effect by increasing the ALKBH5‐mediated m 6 A modification of TRAF4 mRNA, and enhancing TRAF4 translation in an YTHDF1‐dependent manner. TRAF4 in turn promotes ubiquitination of PPARγ and inhibits adipogenesis.